Effectiveness of Tuba Root (Derris elliptica) on Histological Structure of Rabbit Fish Liver - Sekewael, Usi; Leiwakabessy, Fredy; Warella, Juen Carla; Rahaweman, Ayu Christien; Rumahlatu, Dominggus (Universitas Negeri Semarang, 2024)
Rabbit fish (Siganus vermiculatus) is one of the biological resources in the sea that is widely consumed by the people in Maluku. Rabbit fish are caught during low tide with nets or by using natural resources to poison the fish, such as tuba root (Derris elliptica), which contains rotenone to make fish easy to catch. This study aimed to determining the concentration of tuba root extract that was effective against damage to the liver tissue of rabbit fish. Rabbit fish and tuba root were collected from Oma Village, Haruku Island, Central Maluku District, Maluku Province. In the study, a laboratory experiment was conducted in which the tuba root was treated with doses of 0.1 g, 0.3 g, 0.5 g and 1 g with an exposure time of 18 to 24 hours. Data were analyzed using two-way analysis of variance (ANOVA) followed by Duncan's post-hoc test. As a result, the lowest level of liver damage in rabbit fish was observed at a dose of 0.1 g, with a total damage of 7 ± 0.00 and 8.5 ± 0.71. Conversely, the highest level of liver damage was observed at a dose of 1 g, with a total damage of 14 ± 0.00 and 15 ± 0.00. The results of the post hoc test showed a subset value of 0.1 g dose (7.75), 0.3 g dose (9.25), 0.5 g dose (12.00), and 1 g dose (14.50). This research indicates that administering tuba root to rabbit fish can result in damage to the liver's structure. The severity of this damage is contingent upon the dose administered, whereas exposure duration does not affect the level of damage to fish organs.